Do you trust our public protection? Exploring its moderating effect in the relationship between perceived susceptibility and flood preparedness intention - Mohd Rozaimy, Ridzuan; Jamal Rizal, Razali; Ju, Soon Yew; Noor Amira Syazwani, Abd Rahman; Kong, Lai Kuan; Norhidayah, Md Yusof
Frequent flooding in Malaysia has resulted in substantial human casualties and property damage. Pahang, situated on East Coast Peninsular Malaysia, is highly susceptible to significant flood events, especially during the monsoon season. Increasing awareness of the susceptibility to catastrophes has been observed to have a positive influence on individuals’ inclination to acquire knowledge and understanding of disaster preparedness, thereby reducing their vulnerability to such events. This research investigated the correlation between perceived susceptibility, flood preparedness intention, and trust in public protection among a sample of 200 residents from the state. The proposed model underwent testing through the application of the structural equation modelling technique, specifically the partial least squares method. The findings revealed a positive relationship between perceived susceptibility and flood preparedness intention, and this relationship weakened with higher levels of trust in public protection. This study aims to contribute to the body of knowledge regarding flood preparedness in Malaysia, particularly in Pahang. Furthermore, this study is anticipated to assist policymakers in formulating specific policies to help individuals deal with flood situations.